(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
Democracy is based on education according to Socrates (470-390 B.C.) A lack of education leads to election problems. The 2020 presidential election has raised questions of election fraud and rigged software and the integrity of the results. Such questions can be resolved through election technology & security education. Education can put you in a position of knowledge if you find yourself in a discussion on voter fraud. The purpose of this paper is to propose a curriculum for different courses on election security and election technology to educate people. Individuals’ trust of an election can be impacted by education which may overriding propaganda, and fake news. Proposed curriculum also covers misleading election numbers from statistics and Benford’s Law.